Plasmodium falciparum domain mediating adhesion to chondroitin sulfate A: A receptor for human placental infection - Buffet, Pierre A. (The National Academy of Sciences, 1999)
Malaria during the first pregnancy causes a high rate of fetal and neonatal death. The decreasing susceptibility during subsequent pregnancies correlates with acquisition of antibodies that block binding of infected red cells to chondroitin sulfate A (CSA), a receptor for parasites in the placenta. Here we identify a domain within a particular Plasmodium falciparum erythrocyte membrane protein 1 that binds CSA. We cloned a var gene expressed in CSA-binding parasitized red blood cells (PRBCs). The gene had eight receptor-like domains, each of which was expressed on the surface of Chinese hamster ovary cells and was tested for CSA binding. CSA linked to biotin used as a probe demonstrated that two Duffy-binding-like (DBL) domains (DBL3 and DBL7) bound CSA. DBL7, but not DBL3, also bound chondroitin sulfate C (CSC) linked to biotin, a negatively charged sugar that does not support PRBC adhesion. Furthermore, CSA, but not CSC, blocked the interaction with DBL3; both CSA and CSC blocked binding to DBL7. Thus, only the DBL3 domain displays the same binding specificity as PRBCs. Because protective antibodies present after pregnancy block binding to CSA of parasites from different parts of the world, DBL-3, although variant, may induce cross-reactive immunity that will protect pregnant women and their fetuses.